Identifikasi Risiko Teknologi Informasi Pada Layanan Umroh Digital di Indonesia - niswaaa, Niswa Kamila; Thayib, Syarif (LABATILA : Jurnal Ilmu Ekonomi Islam, 2025)
The advancement of information technology has driven digital transformation across various sectors, including religious services such as umrah pilgrimage management. In Indonesia, digital umrah services provide increased efficiency and accessibility through online platforms that cover registration, payment, training, and post-journey reporting. However, this transformation also introduces complex information technology risks that require serious attention. This study aims to identify key risks emerging from digital umrah services, including data security threats, system disruptions, digital fraud, non-compliance with sharia principles, and digital literacy gaps. A descriptive qualitative approach was applied using literature review as the primary method, with content analysis employed to examine relevant academic and regulatory sources. The findings indicate that digital umrah services require a comprehensive risk management system, stronger regulatory frameworks, robust personal data protection, enhanced digital literacy, and strict adherence to sharia principles throughout service operations. These insights are expected to serve as a foundation for developing safer, more inclusive, and religiously compliant digital pilgrimage services.